Seven soil-inhabiting new species of the genus Trichoderma in the Viride clade - Chen, Kai; Zhuang, Wen-Ying (Phytotaxa, 2017)
Seven new species of the genus Trichoderma belonging to the Viride clade are described from soil samples of different regions in China, and named as T. adaptatum, T. beijingense, T. bifurcatum, T. mangshanicum, T. shaoguanicum, T. tardum and T. vulgatum. Their phylogenetic positions are determined by analyses of the combined partial sequences of translation elongation factor 1-alpha and the second largest RNA polymerase subunit encoding genes. Morphology and culture characteristics are observed, described and illustrated in detail. All the new species form green conidia, fit nicely the Viride clade, but differ obviously from any known species of the genus in sequence data, colony features, growth rates, and size of phialides and conidia. Distinctions between the new species and their close relatives are discussed.